Geochemical Properties and Critical Mineral Potential of Ni-Laterite Deposits in Advancing Clean Energy Technology Development - Fatimah, Dian Yesy; Setiawan, Erwin; Prasojo, Adhen Salahudin Al Ayubi; Ulvah, Febria; Kurniawan, Rizki (UIR PRESS, 2024)
Critical elements refer to a group of elements that possess strategic significance and play a vital role in the national economy, as well as in national defense and security. These minerals are at risk of supply disruptions and lack suitable substitutes. In clean energy industries, critical elements are particularly important, especially for electric vehicle components. Aligned with national commitments expressed in the G20 Leaders’ Declaration. Nickel laterite deposits are one of the key sources with high potential for critical elements. This research focuses on critical elements in nickel deposits, which are Ni, Co, Mn, Cr and Al, and their resource potential in Kolaka, Southeast Sulawesi. The methods used are geochemical data, field data, and reference studies. The methods used in the research include literature study, X-Ray Fluorescence (XRF) geochemical analysis of all samples using the Exploratory Data Analysis (EDA) method using Microsoft Excel, Data modelling using scatter plot and heatmap of spearman correlation. The findings indicate that the enrichment of critical elements such as cobalt (Co), manganese (Mn), aluminum (Al), and chromium (Cr) is concentrated in the limonite zone and associated with Fe with various ranges of 0.04-0.14% Co, 0.27-1.13% MnO, 1.03-4.60%Cr2O3, 2.82-9.94% Al2O3 content, whereas nickel (Ni) is enriched in the saprolite zone and associated with Mg with a various range 0.5-3.17%Ni. Overall, the concentration of critical elements other than Ni and Co is typically lower in nickel laterite deposits with high nickel content. With continuous advancements in extraction technologies through research, all zones of laterization in nickel laterite deposits, not just the nickel-rich saprolite zone, could be optimally utilized. This would enhance the potential of nickel laterite deposits as a valuable commodity, contributing significantly to the acceleration of the energy transition towards cleaner energy through clean energy-based technologies.